Inter-Religious Da’wah Communication Overcome Conflict - Noval Setiawan; Nafisatun Hasanah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
This research discusses da'wah communication between religious adherents in overcoming conflict. This problem stems from the existence of a miscommunication between Muslims and Hindus. This research uses the theory of da'wah communication. This is a qualitative research with an interpretative paradigm and a case study approach. Methods of data collection through interviews, observation, and documentation. Meanwhile, data analysis uses data reduction analysis techniques, data presentation, and draws conclusions and verification to see how communication efforts deal with conflicts and their results. The conclusions in this study are, firstly the communication efforts of Islamic community preaching in overcoming conflicts in Dusun Mangir Lor include through group communication such as involving Hindus in social activities. Meanwhile, the communication efforts of Hindus in overcoming conflicts are by being tolerant. Second, the results of inter-religious da'wah communication efforts in overcoming conflicts include stating social identity, social integration, increasing knowledge, finding solutions, creating supervision, and inter-religious relations. The implication in this research is inter-religious harmony.